Tematy polsko-ukraińskie Bohdana Osadczuka w paryskiej „Kulturze” - HOFMAN, Iwona (Przegląd Politologiczny, 2018)
The paper aims to revise the journalistic and political work of Bohdan Osadczuk in the Paris Kultura periodical in order to celebrate his ninetieth birthday. Osadczuk (a.k.a. BEO, J. Czarnomorskyj) formally started cooperation with Jerzy Giedroyæ’s periodical in 1952 finishing it when the monthly was closed in 2000. Taking into consideration the diversity of literary genres employed by Osadczuk one can evidence how important his articles and reviews were, especially those published after 1990. The political changes that affected Poland and Ukraine formed a turning point in Osadczuk’s writing, confirming that he had returned to his role of a chronicler, which characterized him over the time of his involvement with the periodical. This co-author of ‘the eastern concept’ discussed Polish-Ukrainian issues in over a hundred journalistic texts published in the first decade following the ‘fall of the peoples’, and devoted to the symptoms of normalization in Polish-Ukrainian relations and the negative consequences of ignorance concerning mutual prejudices. Osadczuk also recorded his impressions from visits to Ukraine, concentrating on social and cultural matters. He was the last reviewer of the policies of the presidents L. Krawczuk and L. Kuczma. The paper constitutes a review of the issues discussed in B. Osadczuk’s journalism.